2020
DOI: 10.1186/s13550-019-0588-4
|View full text |Cite
|
Sign up to set email alerts
|

Early response monitoring of neoadjuvant chemotherapy using [18F]FDG PET can predict the clinical outcome of extremity osteosarcoma

Abstract: Background To propose a personalized therapeutic approach in osteosarcoma treatment, we assessed whether sequential [18F]FDG PET/CT (PET/CT) could predict the outcome of patients with osteosarcoma of the extremities after one cycle and two cycles of neoadjuvant chemotherapy. Methods A total of 73 patients with AJCC stage II extremity osteosarcoma treated with 2 cycles of neoadjuvant chemotherapy, surgery, and adjuvant chemotherapy were retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…No additional studies were found after screening the references of these articles. Therefore, eight articles evaluating the diagnostic role of 18 F-PSMA-1007 PET/CT in PCa staging were eligible for the systematic review [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The characteristics of these studies selected for the systematic review and including a total number of 369 PCa patients are presented in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…No additional studies were found after screening the references of these articles. Therefore, eight articles evaluating the diagnostic role of 18 F-PSMA-1007 PET/CT in PCa staging were eligible for the systematic review [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The characteristics of these studies selected for the systematic review and including a total number of 369 PCa patients are presented in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the chelator HBED-CC (N,N’-bis [2-hydroxy-5-(carboxyethyl)benzyl] ethylenediamine-N,N’-diacetic acid) used in PSMA-11 is not suitable for the stable complexation with therapeutic radionuclides [ 138 ]. To date, PSMA-617 and PSMA I&T are the most commonly used theragnostic PSMA radioligands because they can be radiolabeled with diagnostic, e.g., 68 Ga and 44 Sc for PET and 111 In for SPECT, as well as therapeutic radiometals [ 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. In an attempt to prolong circulation in the blood and therewith, to increase the dose delivered to tumors and the tumor-to-kidney ratio, PSMA ligands have been structurally modified by adding albumin-binding moieties [ 123 , 132 , 145 , 146 , 147 , 148 , 149 , 150 ].…”
Section: Targeted Radionuclide Therapy Of Prostate Cancermentioning
confidence: 99%
“…However, the overall uptake values were low (SUV max of 0.47 treated versus 0.009 untreated). More recently, Bulat et al reported on the synthesis of 18 F-C2Am of N-5-( 18 F)fluoropentyl)maleimide [ 28 ]. Following the treatment of Colo205 and MDA-MB231 xenografted mice with the TRAILR2 agonist or 5-FU and doxorubicin, 18 F-C2Am generated mean tumour-to-muscle ratios of 6.1 and 10.7 within 2 h of its administration.…”
Section: Membrane-asymmetry Targeting Agentsmentioning
confidence: 99%
“…While 18 F-ML-10 was shown to accumulate in apoptotic MDA-MB-231 and MDA-MB-468 cells 72 h after treatment with paclitaxel in vitro, no significant increase of tracer accumulation was found in comparable murine xenografts following apoptosis induction (as demonstrated by cleaved caspase 3 levels) by paclitaxel [ 43 ]. Following the radiation treatment of human nasopharyngeal carcinoma xenografts (highly differentiated xenografts CNE1 and poorly differentiated xenografts CNE2), the tumour to muscle ratios were statistically different at both 24 and 48 h in CNE1 and CNE2 mice (ratios in CNE2 xeongrafts being higher than those in CNE1 xenografts) [ 44 ].…”
Section: Cell Membrane Acidification Targeting Radioligandsmentioning
confidence: 99%